Medicaid-Insured Patients Exhibit Similar Improvements in Knee Range of Motion Compared to Commercially Insured Patients Despite Inferior Access to Physical Therapy Following ACL Reconstruction - Neufeld, Eric V.; Tarazi, John M.; Wickes, Catherine; Klein, Brandon J.; Colleluori, Melissa A.; Cohn, Randy M.; Goodwillie, Andrew D. (The Journal of Knee Surgery, 2025)
Insurance status has been shown to impact clinical outcomes after several orthopaedic procedures. Current evidence examining the role of insurance provider on outcomes following anterior cruciate ligament (ACL) reconstruction is limited. Therefore, the purpose of this investigation was to explore the effect that insurance carrier had on physical therapy (PT) access, knee range of motion (ROM), and Knee Outcome Survey (KOS) scores. A retrospective cohort study identified patients who underwent ACL reconstruction at an academic health system from January 1, 2019 to December 31, 2021. Patients were partitioned into two cohorts based on their insurance provider: Managed care (MC) or commercial (COM). Outcomes recorded change in knee active range of motion (AROM), passive ROM (PROM), KOS score, and reason for conclusion of PT. Univariate and multivariate analyses were performed by chi-squared tests, Welch's t-tests, as well as multivariable logistic and linear regression with Bonferroni corrections applied to control the family-wise error rate. The study cohort included 149 patients who underwent ACL reconstruction and completed rehabilitation within affiliated PT locations. The MC cohort experienced a longer time until the first PT visit, shorter duration of PT, fewer total PT visits as well as insurance-authorized visits, and a smaller maximum number of visits per patient's benefit. However, there was no difference between cohorts in the number of visits divided over the treatment duration or the number of visits attended over the total number authorized. Both the groups displayed statistically similar improvements in AROM, PROM, and KOS in addition to comparable reasons for concluding PT. Furthermore, regression demonstrated that no insurance parameter predicted changes in AROM, PROM, KOS, or reason for concluding PT. MC-provided patients who underwent ACL reconstruction had inferior access to PT compared with those insured by COM. However, MC and COM yielded a similar percentage utilization of authorized PT visits and number of insurance denials leading to early PT termination. Both the cohorts also demonstrated similar improvements in AROM, PROM, and KOS.
Keywords: anterior cruciate ligament reconstruction; physical therapy access; insurance carrier; outcomes